Performance analysis of gas turbine opeerating with low heating value fuels - Edson Batista da Silva (2012)
Gas turbines are generally designed to operate with a specific fuel type. Power plants usually use gas turbine models which operate with natural gas, but there is the possibility of using other kinds of gaseous fuels. In some instances, a fuel of a different calorific value may be available near the power plant site, making the use of the fuel of interest to the plant owner. These fuels can be gases obtained from steel (from blast furnaces and coking plants), from gasification processes of coal or biomass, among others. In this work, a performance analysis on a gas turbine, which was originally designed to run on natural gas, was carried out after changing to lower calorific value fuels. For the purpose of this study, a well known gas turbine performance calculation program was used named GasTurb11. A gas turbine model was created and calculated at design point. This model was defined as the reference gas turbine. Off-design performance studies were done to adjust the reference gas turbine with data from the chosen gas turbine. A good agreement was obtained between the results of the model operating with natural gas at off-design point and the data available from literature for the reference gas turbine. After the validation process, further performance tests were conducted while changing the fuel calculation value. A reduction in the compressor';s surge margin was identified when using the fuels studied. Two strategies are adopted in order to study the effects of the surge margin: the first by extracting a portion of the air at the compressor exit in order to recover the surge margin, and the second strategy was to establish a fixed value for the surge margin. These control strategies proved to be technically feasible and ensured that the gas turbine operated safely at off-design point.